2016
DOI: 10.1086/684552
|View full text |Cite
|
Sign up to set email alerts
|

Reading and Math Achievement among Low-Income Urban Latino Youth: The Role of Immigration

Abstract: Using data from a household-based, stratified random sample of youth and their caregivers from low-income inner-city neighborhoods, this study examined the variability in the academic achievement of Latino youth. The results indicate a significant advantage in reading achievement for first- and second-generation immigrant youth, as compared to the third generation, which persisted even after controlling for important child, parenting, human capital, neighborhood, and demographic covariates. Follow-up analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…This would entail an intergenerational study of immigrant pupils that could potentially identify differences in educational outcomes. Past research has shown that this is a promising area that accounted for variability in immigrant pupils' academic achievement in the American context (Guttmannova, 2016). Further studies should analyze whether the positive effect of social capital on mathematics achievement that we identified in this article is present in other cognitive areas, such as language (Larwin, 2010).…”
Section: Discussionmentioning
confidence: 72%
“…This would entail an intergenerational study of immigrant pupils that could potentially identify differences in educational outcomes. Past research has shown that this is a promising area that accounted for variability in immigrant pupils' academic achievement in the American context (Guttmannova, 2016). Further studies should analyze whether the positive effect of social capital on mathematics achievement that we identified in this article is present in other cognitive areas, such as language (Larwin, 2010).…”
Section: Discussionmentioning
confidence: 72%
“…As a result, engaging first-generation Latino immigrants in research studies can be difficult due to lack of trust of government, immigration concerns, and lack of English proficiency (Guttmannova, 2016). Studies show that many Latino immigrant families view education as a primary means by which they can reconstruct their lives for a better future (Achinstein, Curry & Ogawa, 2015;Vesely, Goodman, Ewaida, & Kearney, 2015), as education can help to change financial and social constructs that hold them back (Alfaro, & Umaña-Taylor, 2015;Patel et al, 2016).…”
Section: Latinos In the Midwestmentioning
confidence: 99%